Industrial furan and its biological effects on the body systems. Issue 5 (31st July 2018) - Alizadeh, Mohammad; Barati, Meisam; Saleh‐Ghadimi, Sevda; Roshanravan, Neda; Zeinalian, Reihaneh; Jabbari, Masoumeh
Abstract: Furan as a product of thermal processing is found in many foods and beverages. In vitro and in vivo genotoxicity was positive for furan, also when metabolic preconditions for the formation of Z‐2‐butene‐1, 4dialdehyde (BDA), the reactive compound, was met. However, in major studies, high doses represented the genotoxic effect. Moreover, data on toxicity in different cells and organs are inconsistent. For preparing remarkable risk assessments in human, providing bioassay data is necessary. We aimed to review available evidences about furan and BDA. A vast number of studies have been published on toxicity of furan in vitro and in vivo. Thus, we present a comprehensive review on the current status of furan in inducing toxic effects in different body systems, and possible mechanisms involved in the negative effects of this compound. In this article, furan mitigation procedures in foods have been taken into account. Practical applications From industrial point, furan is repeatedly used as an intermediate chemical in the process of producing some compounds such as resins, lacquers, pesticides and drugs. Furthermore, it is common as a side‐product of high‐energy radiation and thermal processes in food production. The current study focused on the effects of furan on the body organs. Furthermore, furan mitigation procedures in foods have been addressed in the current study. Nearly all previous studies on the industrial furan demonstrated that it has adverse health effects on the organs of the body. In order to prove specific results, further studies regarding furan risk assessment is of great importance.